Divergence of the bZIP Gene Family in Strawberry, Peach, and Apple Suggests Multiple Modes of Gene Evolution after Duplication - Xiao-Long Wang; Yan Zhong; Zong-Ming Cheng; Jin-Song Xiong (International Journal of Genomics)
The basic leucine zipper (bZIP) transcription factors are the most diverse members of dimerizing transcription factors. In the present study, 50, 116, and 47 bZIP genes were identified in Malus domestica (apple), Prunus persica (peach), and Fragaria vesca (strawberry), respectively. Species-specific duplication was the main contributor to the large number of bZIPs observed in apple. After WGD in apple genome, orthologous bZIP genes corresponding to strawberry on duplicated regions in apple genome were retained. However, in peach ancestor, these syntenic regions were quickly lost or deleted. Maybe the positive selection contributed to the expansion of clade S to adapt to the development and environment stresses. In addition, purifying selection was mainly responsible for bZIP sequence-specific DNA binding. The analysis of orthologous pairs between chromosomes indicates that these orthologs derived from one gene duplication located on one of the nine ancient chromosomes in the Rosaceae. The comparative analysis of bZIP genes in three species provides information on the evolutionary fate of bZIP genes in apple and peach after they diverged from strawberry.